Simultaneous quantification of 12 veterinary drug residues in fishery products using liquid chromatography-tandem mass spectrometry. (30th June 2021) - Jung, Hae-Ni; Park, Da-Hee; Yoo, Kyung-Hee; Cho, Hee-Jung; Shim, Jae-Han; Shin, Ho-Chul; Abd El-Aty, A.M.
Highlights: An analytical method for detection of 12 anthelmintics in fishery products was developed. Analysis was carried out using liquid chromatography-tandem mass spectrometry. The established method exhibited satisfactory validation parameters. None of the market samples were tested positive for the monitored analytes. The reported protocol could be used for xenobiotic quantification in aquaculture. Abstract: Herein, an analytical method was developed for simultaneous determination of 12 anthelmintics (closantel, niclosamide, nitroxynil, rafoxanide, cymiazole, fluazuron, levamisole, morantel, praziquantel, pyrantel, thiophanate, and trichlorfon) in fishery products (eel, flatfish, and shrimp) using liquid-liquid extraction coupled with liquid chromatography-tandem mass spectrometry. A reversed-phase analytical column was then used to separate the analytes from various matrices. Linear matrix-matched calibration curves were generated with coefficients of determination ≥ 0.9935. Recovery rates at three spiking levels (5, 10, and 20 µg/kg) ranged between 61.58% and 119.37% with relative standard deviations ≤ 19.05%. Limits of detection were in the range of 0.3–1.6 μg/kg, whereas limits of quantification ranged between 1.0 and 5.0 μg/kg. The matrix effect was moderate with values ranging from −99.47% to 51.98%. Matrices procured from large markets tested negative for the 12 anthelmintics. The developed method proved amenable to real sample testing and can be used for simultaneous determination of target analytes in aquatic products.